Continuous or interrupted suture technique for hepaticojejunostomy? A national survey - Brunner, Maximilian; Stockheim, Jessica; Krautz, Christian; Raptis, Dimitrios; Kersting, Stephan; Grützmann, Robert; Weber, Georg (BMC Surgery, 2018)
BACKGROUND: Hepaticojejunostomy is commonly used in hepato-bilio-pancreatic surgery and a crucial step in many surgical procedures, including pancreaticoduodenectomy. The most frequently used techniques are the interrupted suture and the continuous suture technique. Currently, there is no data available in regard to the utilization of these techniques. METHODS: In total, 102 hospitals in Germany were invited between September and November 2017 to participate in this survey. Using a paper-based questionnaire, data were collected on surgical technique and complication rates of hepaticojejunostomies. RESULTS: A total of 77 of the 102 addressed hospitals (76%) participated in the survey. On average, each hospital performed 71 hepaticojejunostomies per year - most often in the context of pancreaticoduodenectomy (71%). 24 (31%) hospitals exclusively use an interrupted suture technique, 7 (9%) hospitals solely a continuous suture technique, 3 (4%) hospitals perform a combination of continuous and interrupted suture technique and 43 (56%) hospitals decide on one of both techniques depending on intraoperative findings. According to the participants in this survey, the continuous suture technique is significantly faster than the interrupted suture technique in hepaticojejunostomy (p = 0,015). There were no significant differences in the overall complication rate (p = 0,902) and insufficiency rate (p = 1,000). CONCLUSIONS: In Germany, there is a heterogeneity in the technique used to create a hepaticojejunostomy. As our survey suggests that the use of continuous suture technique may offer an advantage in time without jeopardizing patient outcomes, the different techniques should be compared in a randomized controlled study.
EVALuna2:210706